Persepsi Tokoh Agama di Desa Ngile Kecamatan Tulakan Kabupaten Pacitan tentang Perbankan Syariah - Ana Silmi Kaffata; Ruliq Suryaningsih (Falahiya: Journal of Islamic Banking and Finance, 2024)
Introduction: The aim of this research is to determine and analyze perceptions, factors that influence perceptions and the impact of the perceptions of religious figures in Ngile Village regarding sharia banking. Research Methods: The type of research used in this research is field research. Data collection techniques through interviews, observation and documentation. The data validity technique uses source triangulation. Data analysis techniques use data reduction techniques, data presentation, and drawing conclusions. Results: The results of this research show that the perception of religious leaders in Ngile Village still considers sharia banks to be the same as conventional banks. In this research, the need factor is the main internal factor that really influences figures to use sharia banks, where religious figures use sharia banks for their Hajj needs. Conclusion: Religious figures still use conventional banks for daily financial transactions. People who have heard information about sharia banking from religious figures will think the same as these figures, in other words religious figures influence the people of Ngile Village.